“WALI SONGO” PERINTIS PENDIDIKAN ISLAM DI INDONESIA(Masa Awal Perkembangan Islam di Jawa) - Asgar Marzuki; Bahaking Rama; Mukjizah Mukhtar Lutfi (CV. ADIBA AISHA AMIRA, 2023)
Da'i is a symbol of proclaiming and carrying Islamic teachings, sincerely and selflessly for the efforts of li'ilai Kalimatillah (to elevate the word of Allah). Moving around the world with wealth and self without asking for wages, as a manifestation of the verses of the Koran, Q.S. as-Shaff/61:11